2022
DOI: 10.3390/antiox11102021
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy: Are lncRNAs New Molecular Players and Targets?

Abstract: The growing incidence of diabetes mellitus worldwide implies the increasing prevalence of several related macro- (e.g., hypertension and atherosclerosis) and micro-vascular (e.g., nephropathy and retinopathy) complications. Notably, diabetic retinopathy (DR) is the leading cause of blindness in older diabetic patients and can occur with different degrees of severity. Chronic hyperglycemia is the main determinant of the functional damage of retinal cells. The oxidative stress, inflammatory factors and vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 189 publications
(336 reference statements)
0
3
0
Order By: Relevance
“…The maternally expressed gene 3 (MEG3) is a tumor repressor lncRNA [ 38 ]. The expression of lncRNA-MEG3 was decreased in endothelial cells subjected to hydrogen peroxide, and in streptozotocin-induced diabetic mice [ 39 ]. Depleting lncRNA-MEG3 increases the phosphorylation of PI3K and Akt, suggesting its role in angiogenesis.…”
Section: Lncrnas and Proliferative Retinopathiesmentioning
confidence: 99%
“…The maternally expressed gene 3 (MEG3) is a tumor repressor lncRNA [ 38 ]. The expression of lncRNA-MEG3 was decreased in endothelial cells subjected to hydrogen peroxide, and in streptozotocin-induced diabetic mice [ 39 ]. Depleting lncRNA-MEG3 increases the phosphorylation of PI3K and Akt, suggesting its role in angiogenesis.…”
Section: Lncrnas and Proliferative Retinopathiesmentioning
confidence: 99%
“…Thus, HG-increased HIPK2 expression correlates One of the complications of diabetes is diabetic retinopathy (DR), which is also the primary cause of blindness in the world [106]. An interesting link between HIPK2 and DR has been depicted due to HIPK2 regulation by microRNA (miRNA), which is usually involved in DR vascular complications [107]. Taking advantage of a previous study in which the authors found that miR-423-5p levels are elevated in the plasma of DR patients [108], the authors, following this, evaluated the role of HG in this regulation.…”
Section: Hipk2 and Diabetes Complicationsmentioning
confidence: 99%
“…Extensive research has revealed the dysregulation of various ncRNAs, including microRNAs (miRNAs), circular RNAs (circRNAs), and long non‐coding RNAs (lncRNAs), in conditions such as glaucoma, cataract, diabetic retinopathy, and ocular tumors (Rong et al 2021; Zhang et al 2020a). These ncRNAs have been shown to impact important cellular processes, including angiogenesis, inflammation, cell proliferation, and apoptosis, which are critical in the development and progression of ocular diseases (Cataldi et al 2021). Understanding the involvement of ncRNAs in ocular diseases holds promise for the development of novel diagnostic tools and therapeutic strategies targeting these ncRNA molecules (Shi et al 2023).…”
Section: Introductionmentioning
confidence: 99%